Occupational Drill Down of Training Needs in the Milwaukee Metro Area - (:unkn) unknown (My University, 2006)
This report provides an occupational drill down focusing on training needs identified for specific occupations and job titles identified by employers participating in the May 2006 Survey of Job Openings, conducted by the Employment and Training Institute for the Private Industry Council of Milwaukee County. Detailed job openings data are provided for six occupational areas where technical training is required: health care workers, manufacturing openings, computer specialists, selected service occupations, clerking and administrative support jobs, and jobs requiring a valid driver’s license or a commercial driver’s license.
Keywords: job openings; job skills; spatial mismatch